A novel 9-level fourfold-boost switched capacitor inverter (N9L-FBSCI) configuration utilizing fewer components and optimized active switches - N. Subhashchandrabose; I. Kumaraswamy (Institute of Advanced Engineering and Science, 2026)
Multilevel inverter (MLI) topologies are more important in high-voltage applications where the most common design tends to have significant disadvantages, including being very component when it comes to the switch voltage stress, control scheme, and also not self-voltage balanced. These problems lead to higher cost, lower efficiency, and lower reliability. This paper will therefore develop a new nine-level fourfold-boost switched capacitor inverter (N9L-FBSCI) without increasing the number of components but ensures greater voltage gains and ease of use. It uses only one DC source, eight active switches, and two capacitors with a self-balancing mechanism of the voltage, avoiding extra balancing of the voltage. A four fold voltage gain is achieved using fewer switching devices per stage and less blocking voltage to control across switches. An efficient control is achieved by a level-shifted phase disposition PWM (LS-PDPWM) technique. Analytical and comparative testing against recent MLI design proves that the topology proposed has better voltage boosting and efficiency using the least number of components. Simulation and experimental verification prove the practical efficiency of the N9L-FBSCI, which can achieve a 400 V peak output with low total harmonic distortion. The topology has a high potential in renewable and industrial fields with cost effective high performance. Experimental and simulation data support an output voltage of 400 V at an output load current of 2 A with RL loading (100 Ω, 100 mH) delivering 400 W power output. The efficiency in the case of the inverter reaches its peak at 97.84% and voltage and current total harmonic distortion (THD) of 16% and 6%, correspondingly. The present proposed N9L-FBSCI has a better voltage gain and fewer components than available nine-level topologies without altering the delight of the wave position.